Feasibility of Minimum Competency Assessment Questions (MCA) Numeracy Based on Higher Order Thinking Skills (HOTS) to Improve Student Competence - Hari Sugiharto Setyaedhi (LPPM Undiksha, 2025)
The Program for International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS) tests show that the mathematics achievement of Indonesian students is very low. This research aims to produce a PISA model product in the form of Minimum Competency Assessment (MCA) numeracy questions based on Higher Order Thinking Skills (HOTS) and test its suitability as a measuring tool so that it can improve student competence. The research subjects were education evaluation experts and high school students. Data collection techniques are obtained through tests, observations, interviews and questionnaires. Data were analyzed using quantitative descriptive. The development model uses ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The results of the research on MCA numeracy were declared feasible as follows: validation results by educational evaluation experts obtained a score of 97.3%, categorized as very feasible; individual trial results of 80% were categorized as feasible; small group trials of 90% were categorized as very feasible. The conclusion of the research on developing HOTS-based MCA questions is that it is very suitable to be used as a test tool to test student competency. The implications of the results of this research regarding MCA can improve student competence in high school.